The determinants of voluntary climate change disclosure commitment and quality in the banking industry - Caby, Jérôme; Ziane, Ydriss; Lamarque, Eric (Technological forecasting & social change, 2020)
•We identify determinants of banks’ voluntary climate change disclosure and quality.•Based on data of 117 banks worldwide, banks want to be seen as good citizens.•However, the picture is unclear for rigorous carbon disclosure.•Our results support stakeholder and legitimacy theory as well as greenwashing.•There is a gap between displaying responsible behavior and actual practice. Banks are both impacted by climate change and crucial for the implementation of sound practices and behaviors to combat climate change. The aim of this research is to identify the determinants of banks’ voluntary climate change disclosure and the quality of that disclosure. Using data on 117 banks from 40 developed and developed countries around the world, we use ordinary least square regression and multivariate logit analysis to show that country-level and bank-level characteristics are much better predictors of bank commitment to voluntary carbon disclosure initiatives and environmental scores than they are of carbon disclosure quality. Banks want to project themselves as good citizens when they are located in a developed and environmentally friendly country, profitable, less risky, and subject to multiple-listing constraints. However, the picture is unclear when it comes to the implementation of rigorous carbon disclosure. This study extends the current state of knowledge on the impacts of size and country-level characteristics on carbon disclosure, finding that size and national context are not independent of carbon disclosure.